West Africa Climate-Smart Villages AR4D sites: 2016 Inventory - Bonilla Findji, Osana; Ouédraogo, Mathieu; Partey, Samuel T.; Dayamba, Sidzabda Djibril; Bayala, Jules; Zougmoré, Robert B. (2017)
Inventory of CSA practices in West Africa's Climate-Smart Villages.